Model Pelaksanaan Program Karang Taruna dalam Pembinaan Tingkah Laku Remaja di Desa Midang Kecamatan Batulayar Kabupaten Lombok Barat - Sumiati, Sumiati; Maimun, Maimun; Nuruddin (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2023)
This study explores the implementation model of the Karang Taruna program in fostering youth behavior in Midang Village, Batulayar District, West Lombok, during the 2022/2023 academic year. Karang Taruna plays a crucial role as a youth organization in guiding and shaping youth to avoid negative influences amid globalization and technological advancement. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. Findings reveal that the program covers social, religious, educational, sports, and entrepreneurship activities, all of which contribute positively to youth character development. Supporting factors include strong community involvement, village government support, and encouragement from local leaders. Conversely, challenges arise from limited funding, inadequate facilities, and low participation of some youth. Overall, Karang Taruna in Midang Village demonstrates an effective development model that successfully guides youth toward positive, productive, and responsible behavior.